Forgiveness Therapy in Developing Subjective Well-Being of Homosexual Clients at Yayasan Peduli Sahabat Cibinong Bogor - Muhammad Fikri Maulana (JOUSIP: Journal of Sufism and Psychotherapy, 2021)
A homosexual has many problems in his life, including confusion of self-identity and social intolerance from the environment, because many people put aside human values â€‹â€‹in viewing the reality of homosexuals, so that society gives all â€œstampsâ€, such as homosexuals as pathological, anomaly, or abnormal. . This study aims to find out more about forgiveness therapy as a form of developing subjective well-being of homosexual clients at â€œYayasan Peduli Sahabat Cibinong Bogorâ€. The research method used in this study is a qualitative research method. The type of research used is field research. Researchers went directly to the research site at Yayasan Peduli Sahabat Cibinong Bogor in obtaining data and engaging with the subject directly. The primary data sources in this study were counselors or client companions, and homosexual clients at the Peduli Sahabat Foundation. The data collection technique was done by interview, observation, and documentation. The data that has been obtained is then analyzed descriptively using the Miles and Huberman interactive model which consists of data reduction, data presentation, and verification. The results showed that the subjective well-being of homosexual clients at Yayasan Peduli Sahabat experienced a good development of conditions after using forgiveness therapy. This is marked by a state of cognition or a new perspective on himself, which initially homosexual clients were unable to take lessons, considered failure, humiliation, but now they have changed such as being able to take lessons, the meaning of life, and life satisfaction.